Abandonment of Human Immunodeficiency Virus Preexposure Prophylaxis Prescriptions at Retail Pharmacies—United States, 2019. (8th January 2022) - Huang, Ya Lin A; Zhu, Weiming; Carnes, Neal; Hoover, Karen W
Abstract: We analyzed a national pharmacy database to estimate the annual number of persons who abandoned preexposure prophylaxis (PrEP) prescriptions and assessed associated factors. About 9% of persons prescribed PrEP abandoned prescriptions in 2019; abandonment was associated with sex, age, insurance type, black race/ethnicity, and drug copayment amount.